2019
DOI: 10.3390/genes10110937
|View full text |Cite
|
Sign up to set email alerts
|

NF-YA Overexpression in Lung Cancer: LUSC

Abstract: The CCAAT box is recognized by the trimeric transcription factor NF-Y, whose NF-YA subunit is present in two major splicing isoforms, NF-YAl (“long”) and NF-YAs (“short”). Little is known about the expression levels of NF-Y subunits in tumors, and nothing in lung cancer. By interrogating RNA-seq TCGA and GEO datasets, we found that, unlike NF-YB/NF-YC, NF-YAs is overexpressed in lung squamous cell carcinomas (LUSC). The ratio of the two isoforms changes from normal to cancer cells, with NF-YAs becoming predomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 53 publications
2
24
0
Order By: Relevance
“…The first, GSE40419, was derived from a Korean study of 89 LUAD [25]-mRNA levels of NF-YA were found to be substantially increased in tumors (p-value 10 −11 ); NF-YB was decreased (p value 10 −8 ) and NF-YC was unchanged ( Figure 1B). The second study was derived from data on 198 NSCLC patients, mostly from Sweden [24], which we previously reclassified using signature genes in 78 LUSC and 91 LUAD [23]; in the current study, we focused on LUAD samples, and showed that NF-YA, but not the HFD subunits, was globally increased ( Figure 1C). In conclusion, we confirmed NF-YA overexpression in LUAD, a decrease of NF-YB, and normal expression of NF-YC.…”
Section: Nf-ya Was Overexpressed In Lung Tumorsmentioning
confidence: 72%
See 2 more Smart Citations
“…The first, GSE40419, was derived from a Korean study of 89 LUAD [25]-mRNA levels of NF-YA were found to be substantially increased in tumors (p-value 10 −11 ); NF-YB was decreased (p value 10 −8 ) and NF-YC was unchanged ( Figure 1B). The second study was derived from data on 198 NSCLC patients, mostly from Sweden [24], which we previously reclassified using signature genes in 78 LUSC and 91 LUAD [23]; in the current study, we focused on LUAD samples, and showed that NF-YA, but not the HFD subunits, was globally increased ( Figure 1C). In conclusion, we confirmed NF-YA overexpression in LUAD, a decrease of NF-YB, and normal expression of NF-YC.…”
Section: Nf-ya Was Overexpressed In Lung Tumorsmentioning
confidence: 72%
“…GSE81089 is a dataset of 198 NSCLC; using 42 genes validated classifier [27], we previously sub-classified samples in LUAD and LUSC [23]. This specifically identified 91 LUAD samples, which are analyzed in this study.…”
Section: Rna-seq Datasetsmentioning
confidence: 99%
See 1 more Smart Citation
“…In endometrial tissues, the exclusive presence of NF-YAl observed in benign samples suggested that it may represent a marker of differentiation, in opposition to NF-YAs, which is expressed into cancer tissues and linked to poorly differentiated cells [26]. In breast and lung cancers, the ratio Cells 2020, 9, 760 4 of 28 between NF-YAl/NF-YAs isoforms is dramatically shifted towards NF-YAs [27,28]. Despite this, partitioning of breast tumors according to NF-YAl/NF-YAs ratio highlighted a unique category with a high NF-YAl/NF-YAs ratio, that is NF-YAl high /Claudin low subclass, composed by more aggressive tumors prone to metastasize [27].…”
Section: Nuclear Transcription Factor Y (Nf-y)mentioning
confidence: 99%
“…NF-YAs high tumors are enriched in metabolism and cell-cycle up-regulated gene categories. In opposition, these genes are down-regulated in NF-YAl high tumors, characterized by the up-regulation of a promigration signature [28]. While NF-YAs directly activates cell cycle and metabolic genes, NF-YAl indirectly affects promigration genes.…”
Section: Nuclear Transcription Factor Y (Nf-y)mentioning
confidence: 99%